Evaluation of Vision-Related Quality of Life after Autologous Internal Limiting–Membrane Transplantation for Refractory Macular Holes - Yuan D (Dove Medical Press, 2020)
Dongqing Yuan, Weiwei Zhang, Songtao Yuan, Ping Xie, Qinghuai Liu Department of Ophthalmology, First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu Province, People’s Republic of ChinaCorrespondence: Qinghuai LiuDepartment of Ophthalmology, First Affiliated Hospital of Nanjing Medical University, 300 Guangzhou Road, Nanjing, Jiangsu Province 210029, People’s Republic of ChinaEmail liuqh@njmu.edu.cnPurpose: To evaluate the vision-related quality of life of vitrectomy combined with autologous internal limiting membrane (ILM) transplantation for refractory macular holes (MHs).Methods: There were 40 eyes with refractory MHs included, and all eyes received 23 G vitrectomy and ILM peeling with autologous ILM transplantation. Preoperative and postoperative basic conditions were recorded. The Chinese version of the vision-related quality-of-life scale was used to evaluate patients after operation. Quality of life, postoperative visual acuity, and size of MHs before operation were assessed with Spearman rank correlations.Results: All patients were followed up for 3 months after surgery. Mean postoperative best-corrected visual acuity had significantly improved after surgery. Vision-related quality of life of patients after surgery was closely related to the MH index, but negatively correlated with best-corrected visual acuity before and after surgery.Conclusion: The anatomical structure of refractory MHs with ILM peeling combined with autologous ILM transplantation was largely reduced, and the visual acuity of patients improved significantly.Keywords: refractory macular hole, internal limiting membrane transplantation, vision-related quality of life